A Multidisciplinary Study of Traditions on Wife Maintenance from The Social Tradition and The Perspective of the Prophetic Sunnah - Ridwan Ridwan; Ilyas Husti; Hendri Sayuti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
This article is entitled A Multidisciplinary Study of Hadiths on Wife's Maintenance: Social Tradition and the Perspective of the Prophetic Sunnah. This study uses a qualitative method with the approach of analyzing the hadith text through sanad and matan criticism, accompanied by lafadz interpretation (mufradat and word roots) and sharḥ al-ḥadīth. The maqāṣid al-syarī'ah theory is used as the main framework to understand the purpose of the Shari'ah in the obligation of maintenance, while the mubādalah theory and the theory of parallelism are used to interpret the husband-wife relationship in a fair, reciprocal, and functional manner. Classical and contemporary literature is also used as a comparison, especially in seeing how social traditions understand wife's maintenance compared to the perspective of the Prophetic Sunnah. The results confirm that wife maintenance in the Hadith is not just a material obligation, but also includes emotional and spiritual support. The multidisciplinary approach broadens the meaning of the hadith, making it more contextual to the needs of contemporary Islamic family law